Differences in risk factors associated with surgical site infections following two types of cardiac surgery in Japanese patients. Issue 1 (May 2015) - Morikane, K.; Honda, H.; Yamagishi, T.; Suzuki, S.
Summary Background Differences in the risk factors for surgical site infection (SSI) following open heart surgery and coronary artery bypass graft surgery are not well described. Aim To identify and compare risk factors for SSI following open heart surgery and coronary artery bypass graft surgery. Methods SSI surveillance data on open heart surgery (CARD) and coronary artery bypass graft surgery (CBGB) submitted to the Japan Nosocomial Infection Surveillance (JANIS) system between 2008 and 2010 were analysed. Factors associated with SSI were analysed using univariate modelling analysis followed by multi-variate logistic regression analysis. Non-binary variables were analysed initially to determine the most appropriate category. Findings The cumulative incidence rates of SSI for CARD and CBGB were 2.6% (151/5895) and 4.1% (160/3884), respectively. In both groups, the duration of the operation and a high American Society of Anesthesiologists' (ASA) score were significant in predicting SSI risk in the model. Wound class was independently associated with SSI in CARD but not in CBGB. Implants, multiple procedures and emergency operations predicted SSI in CARD, but none of these factors predicted SSI in CBGB. Conclusions There was a remarkable difference in the prediction of risk for SSI between the two types of cardiac surgery. Risk stratification in CARD could be improved by incorporating variables currently available in the existing surveillance systems. Risk index stratification in CBGB could be enhanced by collecting additional variables, because only two of the current variables were found to be significant for the prediction of SSI.